Time Series Analysis of FDI in India Using ARIMA-SVR Hybrid Machine Learning Model - Nagesh, M.; Reddy, D. Mallikarjuna; Kumar, Nitendra; Chaturvedi, Ravi Prakash; Mishra, Annu (Indian Journal of Finance, 2025)
Purpose : This research analyzed the temporal patterns of foreign direct investment (FDI) inflow in India for 53 years (1970–2023) to determine sectoral contributions and the general economic impact of FDI. The emphasis was on enhancing accuracy in time-series forecasting of the economic indicators employing sophisticated statistical and ML techniques. Methodology : Annual FDI inflow data were modeled using three models: Autoregressive integrated moving average (ARIMA), support vector regression (SVR), and a hybrid ARIMA-SVR. ARIMA identified the linear trends, SVR fit the non-linearities, and the hybrid model combined both to take advantage of their complementary strengths. The performance was measured based on mean absolute error (MAE), mean absolute percentage error (MAPE), and root mean square error (RMSE). Findings : The hybrid ARIMA-SVR model delivered better forecasting performance (MAE: 0.29114, MAPE: 21.8581, RMSE: 0.38378) compared to both ARIMA (MAE: 0.36215, MAPE: 28.76416, RMSE: 0.45884) and SVR (MAE: 0.34746, MAPE: 19.85233, RMSE: 0.46288). Practical Implications : The results apprised the importance of hybrid modeling for decision makers, economists and analysts, in generating solid economic forecasts. The method could improve decision-making, policymaking, and investment policies through the delivery of accurate projections of economic trends. Originality : This study was carried out through the application and comparison of ARIMA, SVR, and a hybrid ARIMA-SVR method for long-range FDI prediction in India. It showed the superiority of the hybrid model in combination with linear and non-linear dynamics, providing a methodology framework that can be applied to other economic time series.